PENGARUH PROFITABILITAS, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Euis Dinda Meisyta; Ayus Ahmad Yusuf; Lia Dwi Martika (Jurnal Riset Keuangan dan Akuntansi, 2021)
The purpose of this study is to determine the factors that affect the capital structure. With the independent variables are profitability, asset structure and company size. The population in this study were manufacturing companies in the pulp and paper sub-sector for the period 2015 to 2018. The sampling technique was saturated samples where the samples of this study were 9 companies that met the sampling criteria. The method used is descriptive and verification methods with quantitative data. The data collection technique uses nonparticipating observation. The analysis technique used in this research is descriptive analysis, classical assumption test, panel data regression analysis, coefficient of determination and hypothesis testing using the Eviews Ver 9.0 application program. Hypothesis testing shows that profitability, asset structure and company size simultaneously affect the capital structure. Profitability has a positive and significant effect on capital structure. Asset structure has a positive and significant effect on capital structure. Firm size has a positive and significant effect on capital structure.  Keywords   : Profitability, Asset Structure, Company Size and Structure Capital